ANALISIS PANJANG ANTRIAN DENGAN TUNDAAN PERSIMPANGAN BERSINYAL (STUDI KASUS JALAN S. PARMAN) - Fadhilah Zahrah; Faisal Ashar (Teknik Sipil Universitas Negeri Padang, 2022)
Abstract : The rapid development of the City, the increasing traffic flow in a city requires special attention to avoid anything untoward. The use of private vehicles is one of the impacts in increasing road congestion and intersections in Indonesia. The city of Padang is one of the cities that has many intersections and has a fairly long congestion problem during peak hours, among them is the intersection of the S. Parman road. Vehicle volume surveys are reviewed based on three types, namely MC, LV, and HV, and then calculations are carried out based on the tenure contained in the 1997 MKJI. Simulation using PTV Vissim Student Version 2023 Software where later you will see the movement of traffic flow at the intersection. Research conducted during the week with the determination of busy days and weekends, namely Monday, Thursday, and Saturday. Analysis data in the form of calculating the value of queue length, delay and degree of saturation at the intersection. The calculation results based on the 1997 MKJI showed that the length of the queue on Jalan S. Parman was 5863.77 m, the delay was 1884.69 sec / smp and the degree of saturation was 2.04. The value of the degree of saturation indicates that the intersection is approaching saturated passes which will cause long queues at peak traffic conditions (MKJI, 1997). And the results of the simulation with PTV Vissim Student Version 2023 showed a queue length of 79.75 m and a delay of 102.83 sec / smp with a LOS (Level Of Service) value of F.